Health self‐perception and its association with physical activity and nutritional status in adolescents - Alison Oliveira da Silva; Paula R.B. Diniz; Maria E.P. Santos; Raphael M. Ritti‐Dias; Breno Q. Farah; Rafael M. Tassitano; Luciano M.F.T. Oliveira (Brazilian Society of Pediatrics, 2019)
Objective: To evaluate the association between total physical activities, physical activity in free time and nutritional status with self‐perceived health in adolescents of both genders. Methods: This is a quantitative study that integrates the school‐based, cross‐sectional epidemiological survey with statewide coverage, whose sample consisted of 6261 adolescents (14-19 years old) selected by random conglomerate sampling. Data were collected using the Global School‐based Student Health Survey. The chi‐squared test (χ2) and the Poisson regression model with robust variance were used in the data analyses. Results: It was observed that 27.3% of the adolescents had a negative health self‐perception, which was higher among girls (33.0% vs. 19.0%, p < 0.001). After adjusting for potential confounding factors, it was observed that boys who did not practice physical activity during free time (PR = 1.44, 95% CI: 1.15-1.81) and were classified as insufficiently active (PR = 1.27, 95% CI: 1.04-1.56), as well as girls who did not practice physical activity during free time (PR = 1.15, 95% CI: 1.02-1.29) and were classified as overweight (PR = 1.27, 95% CI: 1.01-1.29) had a greater chance of negative health self‐perception. Conclusion: Behavioral issues may have different effects on health self‐perception when comparing boys with girls. Negative health self‐perception was associated with nutritional status in girls and a lower level of physical activity in boys, and the practice of physical activity in the free time was considered a protective factor against a negative health self‐perception for adolescents of both genders. Resumo: Objetivo: Avaliar a associação entre atividade física total, atividade física no tempo livre e estado nutricional com a autopercepção de saúde em adolescentes de ambos os sexos. Métodos: Trata‐se de um estudo com abordagem quantitativa, que integra o levantamento epidemiológico transversal de base escolar e abrangência estadual, cuja amostra foi constituída por 6.261 adolescentes (14 a 19 anos) selecionados por meio de uma estratégia de amostragem aleatória de conglomerados. Os dados foram coletados a partir do questionário Global School‐based Student Health Survey. O teste de qui‐quadrado (χ2) e o modelo de regressão de Poisson com variância robusta foram usados nas análises dos dados. Resultados: Observou‐se que 27,3% dos adolescentes tinham uma autopercepção de saúde negativa, maior entre as meninas (33,0% vs. 19,0%; p < 0,001). Após o ajuste pelos potenciais fatores de confusão, constatou‐se que tinham maior chance de ter uma autopercepção de saúde negativa os meninos que não praticavam atividade física no tempo livre (RP = 1,44; IC 95%: 1,15‐1,81) e que eram classificados como insuficientemente ativos (RP = 1,27; IC 95%: 1,04‐1,56) e as meninas que não praticavam atividade física no tempo livre (RP = 1,15; IC 95%: 1,02‐1,29) e que eram classificadas como sobrepesadas (RP = 1,27; IC 95%: 1,01‐1,29). Conclusão: Questões comportamentais podem ter diferentes repercussões na autopercepção de saúde quando comparados os meninos e meninas. A autopercepção de saúde negativa esteve associada ao estado nutricional entre as meninas e a um menor nível de atividade física entre os meninos e a prática de atividade física no tempo livre foi tida como fator de proteção para uma autopercepção de saúde negativa para os adolescentes de ambos os sexos. Keywords: Adolescent health, Physical activity, Lifestyle, Prevalence, Palavras‐chave: Saúde do adolescente, Atividade física, Estilo de vida, Prevalência